Susceptibility-weighted imaging in malignant melanoma brain metastasis - Schwarz, Daniel; Hielscher, Thomas; Hassel, Jessica C.; Schlemmer, Heinz-Peter; Platten, Michael; Winkler, Frank; Wick, Wolfgang; Heiland, Sabine; Delorme, Stefan; Bendszus, Martin; Bäumer, Philipp; Breckwoldt, Michael O. (Journal of magnetic resonance imaging, 2019)
Background The value of cerebral susceptibility-weighted imaging (SWI) in malignant melanoma (MM) patients remains controversial and the effect of melanin on SWI is not well understood. Purpose To systematically analyze the spectrum of intracerebral findings in MM brain metastases (BM) on SWI and to determine the diagnostic value of SWI. Study Type Retrospective. Population/Subjects In all, 100 patients with melanoma BM (69 having received radiotherapy [RT] and 31 RT-naïve) and a control group of 100 melanoma patients without BM were included. For detailed analysis of signal characteristics, 175 metastases were studied. Field Strength/Sequence Gradient echo SWI sequence at 1.5, 3.0, and 9.4 T. Assessment Signal characteristics from melanotic and amelanotic BMs on SWI with a focus on blooming artifacts were analyzed, as well as the presence and longitudinal dynamics of isolated SWI blooming artifacts in patients with and without BM. Statistical Tests Chi-squared and Student's t-test were used for contingency table measures and group data of signal and clinical characteristics, respectively. Results Melanotic and amelanotic metastases did not show significant differences of SWI blooming artifacts (38% vs. 43%, P = 0.61). Most metastases without an initial SWI artifact developed a signal dropout during follow-up (80%; 65/81). Isolated SWI artifacts were detected more frequently in patients with BM (20 vs. 9, P = 0.03), of which the majority were found in patients who had received RT (17 vs. 3, P = 0.08). None of these isolated SWI blooming artifacts turned into overt metastases over time (median follow-up: 8.5 months). Similar findings persisted as remnants of successfully treated metastases (88%; 7/8). Data Conclusion We conclude that SWI provides little additional diagnostic benefit over standard T1-weighted imaging, as melanin content alone does not cause diagnostically relevant SWI blooming. Signal transition of SWI may rather indicate secondary phenomena like microbleeding and/or metal scavenging. Our results suggest that isolated SWI artifacts do not constitute vital tumor tissue but represent unspecific microbleedings, RT-related parenchymal changes or posttherapeutic remnants of former metastatic lesions. Level of Evidence: 3 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2019;50:1251-1259.
Gesehen am 14.10.2019